Analysis of overweight and obesity, levels of physical activity and self-esteem of Salvadoran children - Evert Iraheta, Boris (2020)
The objective of this study was to determine the BMI (Body Mass Index), the self-esteem and the level of physical activity of the children of the second cycle of the city of San Salvador. 11 schools participated: 359 (47 %) were girls and 399 (53 %) girls, with an average age of 11.49 ± 1.34 years, a height of 147.11 ± 0.10 cm and a weight of 47.53 ± 13.758 Kg. Weight, height was evaluated, body mass index, the perception of physical activity and self-esteem, through the Physical Activity Questionnaire for Older Children (PAQ-C), and Lawrence Self-Esteem Questionnaire (LAWSEQ). In the results obtained it was found that 29% (n= 227) are underweight, 46.7 % (n= 354) have a healthy weight, 18.3% (n= 139) are overweight and 5% (n= 38) He is obese. In the case of physical activity, the data collected show that 53.7% (n= 407) show values of low physical activity, 43.8% (n= 332) values of physical activity means and 2.5% (n= 19) values of high physical activity. In the case of self-esteem, the data show that 52.9% (n= 401) are in a low self-esteem condition, 43.1% (n= 327) have average self-esteem and 4.0% (n= 30) have high self-esteem values. It is concluded that the data obtained in the variables of body mass index, physical activity level and self-esteem in the students evaluated are alarming, which suggests the need to develop strategies for the intervention of this problem.